Breast Reconstruction Does Not Affect the Survival of Patients with Breast Cancer Located in the Central and Nipple Portion: A Surveillance, Epidemiology, and End Results Database Analysis - Xiong, Mingchen; Liu, Zeming; Lv, Wenchang; Zhao, Chongru; Wang, Yichen; Tan, Yufang; Zhang, Qi; Wu, Yiping; Zeng, Hong (Frontiers in Surgery, 2022)
Background: The tumors in the central and nipple portion (TCNP) are associated with poor prognosis and aggressive clinicopathological characteristics. The availability and safety of post-mastectomy reconstruction in breast cancer patients with TCNP have still not been deeply explored. It is necessary to investigate whether reconstruction is appropriate for TCNP compared to non-reconstruction therapy in terms of survival outcomes. Methods: Using the Surveillance, Epidemiology, and End Results (SEER) database, we enrolled TCNP patients diagnosed between 2010 and 2016. The propensity score matching (PSM) was applied to construct a matched sample consisting of pairs of non-reconstruction and reconstruction groups. Survival analysis was performed with the Kaplan-Meier method. Univariate and multivariate Cox proportional hazard models were applied to estimate the factors associated with breast cancer-specific survival (BCSS) and overall survival (OS). Results: In the overall cohort, a total of 6002 patients were enrolled. The patients with reconstruction showed significantly better BCSS (log-rank, p < 0.01) and OS (log-rank, p < 0.01) than the non-reconstruction group in 832 patients after PSM. However, the multivariate Cox regression model revealed that breast reconstruction was not associated with the worse BCSS and OS of TCNP patients. Conclusions: Our study provided a new perspective showing that breast reconstruction did not affect the survival and disease prognosis in the cohort of TCNP patients from SEER databases, compared with the non-reconstruction. This finding provides further survival evidence supporting the practice of post-mastectomy reconstruction for suitable TCNP patients, especially those with a strong willingness for breast reconstruction.